Study of the Relationship Between Labor Cost and Labor Productivity - Dimitrova, Ivanka; Yankova, Diana (Research Papers, 2020)
The present study examines labor costs, labor productivity and the relationship between them. The aim is to establish the relationship between the rates of change in labor costs and labor productivity in order to reveal the effects of the established relationship and to outline the path towards competitiveness and development of the surveyed enterprises. The main thesis is that the competitiveness of enterprises and the efficiency of the use of human resources depend on the relationship between the rate of change in labor costs and the rate of change in labor productivity.As a result of the research carried out among industrial enterprises from the Rousse Region for the period 2013-2016, the main conclusion is that the average labor cost growth rates outrun the rate of change in average labor productivity. The enterprises could focus their efforts on increasing labor productivity through: selection, training and control of the work of the staff; promotions and bonuses for employees who have contributed to increasing labor productivity; motivating staff through money, providing opportunities for development through investment in education; introducing new and advanced technologies; developing more efficient and competitive productions.